Curatorial Approaches at the Diaghilev Museum of Contemporary Art at Saint-Petersburg State University: Representations of Art in Synchronous and Diachronic Aspects - Yurieva, Tatiana S.; Staniukovich-Denisova, Ekaterina Iu.; Ershov, Gleb Yu. (Actual Problems of Theory and History of Art, 2021)
The article considers the development of curatorial activity and the representation of art in synchronous and diachronic aspects, as well as the reveal of the uniqueness of the first university museum of modern art in Russia. The museum of contemporary art named after S. P. Diaghilev was founded in 2008 based on the Diaghilev Art Centre (1990–2008); currently, it is part of the Exhibits and Collections Management of St. Petersburg University. The paper carries out the comparative analysis of curatorial practices and curatorial strategies used in the organization of cultural events and exhibitions of the museum in different periods. The museum, from the stage of its creation in the 1990s as an art center to the present, is considered in the context of the general idea of establishing museums of contemporary art in Moscow and St. Petersburg. Special attention has been paid to the museum’s activities and projects of recent years, with regard to the new realities of the pandemic, self-isolation, and remote communication. The publication was prepared within the framework of the research work of St. Petersburg State University “HUM_2020 – 2 Curatorial practices and strategies: new opportunities for the representation of contemporary art: 2021”, project ID PURE SPBU 53363805.